High-speed rail network and periodic timetable: a comparative analysis of operational concepts - Drábek, Michal; Drábek, Michal; Mazel, Dominik; Mazel, Dominik; Pospíšil, Jiří; Pospíšil, Jiří (České vysoké učení technické v Praze, 2021)
This paper compares chosen European high-speed railway (HS) networks in terms of their offer of HS passenger service. The criteria chosen for comparison are network topology, degree of service periodicity and degree of coordination between subsequent services. Only services with HS trains are taken into account. As a result, each examined network is classified according to prevailing approach to passenger service – either Line/Service (LS) Approach, where transfer connections are in general not anticipated, or Network (N) approach, with regular (mostly periodic) public transport lines and periodic transfer connections between them. The comparative analysis has shown that geography had crucial impact not only on national (or regional) HS line network, but on the HS operational concept as well. On trunk HS lines, which connect most populated agglomerations in particular country, there is always – at least during peak times – some form of periodic service, despite compulsory seat reservation (except state-owned carriers in Austria and Germany). Half of analyzed networks can be characterized by N approach – at least on trunk HS lines or within central "core" part of HS network. For Czech HS network, authors recommend to define a core network with application of Integrated Periodic Timetable.